2011
DOI: 10.1128/aac.00520-11
|View full text |Cite
|
Sign up to set email alerts
|

The 8-Aminoquinoline Analogue Sitamaquine Causes Oxidative Stress in Leishmania donovani Promastigotes by Targeting Succinate Dehydrogenase

Abstract: The 8-aminoquinoline analogue sitamaquine (SQ) is an oral antileishmanial drug currently undergoing phase 2b clinical trials for the treatment of visceral leishmaniasis. In the present study, we investigated the mechanism of action of this drug in Leishmania donovani promastigotes. SQ causes a dose-dependent inhibition of complex II (succinate dehydrogenase) of the respiratory chain in digitonin-permeabilized promastigotes, together with a drop in intracellular ATP levels and a decrease of the mitochondrial el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 45 publications
2
31
1
Order By: Relevance
“…Studies have detected a significantly larger amount of active-form metacaspase in cells undergoing H 2 O 2 -induced PCD (8), as well as elevated metacaspase gene expression in miltefosine-induced PCD (42). However, studies that report caspase-independent PCD in these parasites might suggest that metacaspase involvement is not essential (13,34). In our study, we found major upregulation of caspase-3/-7-like protease levels in cells following K-09 exposure, and the pretreatment of cells with the caspase-3 inhibitor Ac-DEVD-CHO diminished caspase-3/-7-like protease activity and PS externalization.…”
Section: Discussionmentioning
confidence: 92%
“…Studies have detected a significantly larger amount of active-form metacaspase in cells undergoing H 2 O 2 -induced PCD (8), as well as elevated metacaspase gene expression in miltefosine-induced PCD (42). However, studies that report caspase-independent PCD in these parasites might suggest that metacaspase involvement is not essential (13,34). In our study, we found major upregulation of caspase-3/-7-like protease levels in cells following K-09 exposure, and the pretreatment of cells with the caspase-3 inhibitor Ac-DEVD-CHO diminished caspase-3/-7-like protease activity and PS externalization.…”
Section: Discussionmentioning
confidence: 92%
“…Sytox green dye was used to assess plasma membrane integrity, as described previously, with some modifications (40). Briefly, parasites (1 ϫ 10 7 promastigotes) of the different L. donovani lines (WTM, A, M, S, AS, and SP) were left untreated or treated with increasing concentrations of their corresponding drugs (AmB, MIL, or Sb III ) for 48 h at 28°C in culture medium, washed twice with HBS buffer, and then incubated with 2 M Sytox green for 15 min at 28°C.…”
Section: Chemicalsmentioning
confidence: 99%
“…A combination therapy of miltefosine with amphotericin B or paromomycin is very efficient and could be helpful to treat antimony-resistant VL infections. Sitamaquine is the second oral drug in the development of leishmaniasis treatment [8].…”
Section: Introductionmentioning
confidence: 99%